Maqashid Ash-Sharia Principles In Child Protection - Riska Harnysah Harahap; Risalan Basri Harahap (IAIN Padangsidimpuan, 2022)
Maqashid Asy- Sharia aims to realize the benefit of man in the world and the hereafter. The principle of Maqashid Asy- Sharia consists of maintaining religion (hifzh al-din), nurturing the soul (hifzh al- nafs), Protection of reason (hifzh al-aql), nurturing offspring (Hifzh al-nasl) and maintaining property (hifz al-mal). The formulation of the problem from this study is how the concept of child protection in Law No. 35 of 2014 concerning Child Protection and How the principle of Maqashid Asy-Sharia in Law No. 35 of 2014 concerning Child Protection. The purpose of this study is to find out how the concept of protection of children in Law No. 35 of 2014 concerning Child Protection andTo find out how the principle of Maqashid Asy-Sharia in Law No. 35 of 2014 concerning Child Protection. The theory used in this study is a theory related to the principle of Maqashid Asy- Sharia in law no. 35 of 2014 concerning. Furthermore, the type of research used is library research, using a normative juridical approach. The results of the research obtained, namely, freedom to practice religion, are contained in article 6 of Law No. 35 of 2014, namely that every child has the right to worship according to their religion, thinking, and expression in accordance with their level of intelligence and age under the guidance of parents or guardians.It is found in (hifzh al-din maintains Religion. Children are a generation that needs to be given religious education so that they have a basic foundation in everyday life. Childcare is contained in article 7 of Law No. 35 of 2014, namely parents and families are responsible for nurturing, maintaining, educating, and protecting children. It is called (hifzh al- nafs). The protection of education is contained in article 9 of Law No. 35 of 2014 concerning child protection, namely that every child has the right to obtain education and teaching in order to develop his personality and his level of intelligence with his interests and talents is hifzh al -aql.